Pattern of skin diseases and common drugs prescribed in dermatology OPD of an Indian tertiary care hospital - Gupta, Surabhi; Khan, Wase; Krishna, Arvind (International Journal of Basic & Clinical Pharmacology, 2016)
Background: The pattern of skin diseases varies from one country to another and across different parts within the same country. The prevalence of skin disease in the general population varies from 11.16 % to 63 %. Patients in their second and third decades of age form the largest group of population. A proper treatment is essential for cure and control of these diseases. The aim of the study was to find the pattern of skin diseases in Meerut district of western UP and common group of drugs prescribed for them. Methods: It was a prospective, observational, single center study. The relevant data was collected from OPD prescriptions by taking photographs of the prescriptions and details were filled in the predesigned proforma. Results: A total of 500 OPD prescriptions were collected and analyzed for demographic profile, disease incidence and drug prescription. Three most common conditions observed were tinea (15.25%), acne (12.36%), drug induced cutaneous reactions (10.11%). Antifungals (19.4%), Antibiotics (17.6%), Antihistamines (15.9%) and Corticosteroids (9.4%) were the most common class of drugs prescribed. Dosage forms prescribed were mostly topical (51.2%) in the form of ointments, creams, lotions, shampoo, powders. Conclusions: From our study we found out that tinea (15.25%) and acne (12.36%) were more common in this region and antifungals were most the commonly prescribed group of drugs (19.4%). Number of drugs/prescription was much higher (4.1) than the recommended limit of 2 approved by WHO and practice of polypharmacy was also commonly seen.